2010
DOI: 10.1051/0004-6361/201015137
|View full text |Cite
|
Sign up to set email alerts
|

Lithium depletion in solar-like stars: no planet connection

Abstract: We have determined precise stellar parameters and lithium abundances in a sample of 117 stars with basic properties very similar to the Sun. This sample selection reduces biasing effects and systematic errors in the analysis. We estimate the ages of our sample stars mainly from isochrone fitting but also from measurements of rotation period and X-ray luminosity and test the connection between lithium abundance, age, and stellar parameters. We find strong evidence for increasing lithium depletion with age. Our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
188
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(203 citation statements)
references
References 55 publications
14
188
1
Order By: Relevance
“…The ratio of stars with lithium to stars without detectable lithium is 8/3 = 2.6, which could reflect the fact that stars with lower log g are younger. Lithium depletion as a function of the age of stars is discussed by Baumann et al (2010) and Carlos et al (2016). On the other hand, we might expect to see the effects of increased shearing in a deeper convective envelope here.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The ratio of stars with lithium to stars without detectable lithium is 8/3 = 2.6, which could reflect the fact that stars with lower log g are younger. Lithium depletion as a function of the age of stars is discussed by Baumann et al (2010) and Carlos et al (2016). On the other hand, we might expect to see the effects of increased shearing in a deeper convective envelope here.…”
Section: Discussionmentioning
confidence: 74%
“…Luck & Heiter (2006) found no differences between the lithium abundances of stars with and without planets. Baumann et al (2010) showed that for solar-like stars there are no statistical correspondence between the lithium abundances and age for stars with and without planets. Thus, the lithium abundance in stellar atmospheres is not affected by the presence of a planet near to a star.…”
Section: Introductionmentioning
confidence: 99%
“…Adibekyan et al 2012a) with some curious trends being a strong matter of debate concerning e.g. the abundances of the light element lithium (Israelian et al 2009;Baumann et al 2010;Sousa et al 2010;Ghezzi et al 2010b) or specific trends including other elemental abundances (e.g. Ramírez et al 2010;González Hernández et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…M67 is relatively nearby (∼900 pc) and is only little affected by interstellar extinction, which allows detailed spectroscopic studies of its main-sequence stars. The depleted Li abundance of the Sun seems rather representative of solar-twins in the Galactic field (Baumann et al 2010). M67 also seems to contain Li-depleted G stars (Pasquini et al 1997).…”
Section: Introductionmentioning
confidence: 99%